ASDB: database of alternatively spliced genes - Dralyuk, I. (Oxford University Press, 2000)
Version 2.1 of ASDB (Alternative Splicing Data Base) contains 1922 protein and 2486 DNA sequences. The protein entries from SWISS-PROT are joined into clusters corresponding to alternatively spliced variants of one gene. The DNA division consists of complete genes with alternative splicing mentioned or annotated in GenBank. The search engine allows one to search over SWISS-PROT and GenBank fields and then follow the links to all variants. The database can be assessed at the URL http://cbcg.nersc.gov/asdb